Factor-Reduced Human Induced Pluripotent Stem Cells Efficiently Differentiate into Neurons Independent of the Number of Reprogramming Factors - Andreas Hermann; Jeong Beom Kim; Sumitra Srimasorn; Holm Zaehres; Peter Reinhardt; Hans R. Schöler; Alexander Storch (Hindawi Limited, 2016)
Reprogramming of somatic cells into induced pluripotent stem cells (iPSCs) by overexpression of the transcription factors OCT4, SOX2, KLF4, and c-Myc holds great promise for the development of personalized cell replacement therapies. In an attempt to minimize the risk of chromosomal disruption and to simplify reprogramming, several studies demonstrated that a reduced set of reprogramming factors is sufficient to generate iPSC. We recently showed that a reduction of reprogramming factors in murine cells not only reduces reprogramming efficiency but also may worsen subsequent differentiation. To prove whether this is also true for human cells, we compared the efficiency of neuronal differentiation of iPSC generated from fetal human neural stem cells with either one (OCT4; hiPSC1F-NSC) or two (OCT4, KLF4; hiPSC2F-NSC) reprogramming factors with iPSC produced from human fibroblasts using three (hiPSC3F-FIB) or four reprogramming factors (hiPSC4F-FIB). After four weeks of coculture with PA6 stromal cells, neuronal differentiation of hiPSC1F-NSC and hiPSC2F-NSC was as efficient as iPSC3F-FIB or iPSC4F-FIB. We conclude that a reduction of reprogramming factors in human cells does reduce reprogramming efficiency but does not alter subsequent differentiation into neural lineages. This is of importance for the development of future application of iPSC in cell replacement therapies.